Excessive alcohol consumption favours high risk polyp or colorectal cancer occurrence among patients with adenomas: a case control study. Issue 1 (1st January 2002) - Bardou, M; Montembault, S; Giraud, V; Balian, A; Borotto, E; Houdayer, C; Capron, F; Chaput, J-C; Naveau, S
Abstract : Background and aims: Excessive alcohol consumption is a risk factor for developing colorectal adenomas. This study aimed to investigate the influence of excessive alcohol consumption on the occurrence of high risk polyps (adenoma ≥10 mm, villous component, high grade dysplasia) or colorectal cancer among patients with at least one colonic adenoma. Patients and methods: Three groups of patients with at least one colorectal adenoma were included in a case control study: 401 heavy drinkers (group HD, mean daily alcohol intake 117 (SD 4) g/day for a mean duration of 22 (SD 0.6) years), aged 57 (0.5) years (78% men); 152 patients suffering from irritable bowel syndrome (IBS), aged 61 (0.9) years (57% male); and 108 patients with a family history (FH) of colorectal adenoma or cancer, aged 55 (1) years (64% male). Exclusion criteria were: anaemia, haematochezia, personal history of colorectal adenoma or cancer, and for groups HD and IBS a family history of colorectal adenoma and/or cancer. Relative risks were estimated by the odds ratio (OR) using a logistic regression model and were expressed with 95% confidence interval (CI). Results: After age and sex adjustment, the likelihood of having an adenoma ≥10 mm was higher in group HD than in the IBS group (OR 1.8, 95% CI (1.2–2.7)) and the likelihood of having high risk adenomas or cancer was higher in group HD compared with the IBS group (OR 1.6, 95% CI (1.2–2.1)) and the FH group although this was not significant (OR 1.6, 95% CI (0.97–2.6) (p=0.081); 90% CI (1.03–2.4)). After age and sex adjustment, the likelihood of having an adenoma with high grade dysplasia or cancer was higher in group HD than in the IBS group (OR 1.7, 95% CI (1.02–2.8)) or group FH, although this was not significant (OR 3.7, 95% CI (0.98–15) (p=0.076); 90% CI (1.10–12.47)). Conclusion: In patients with at least one colorectal adenoma, excessive alcohol consumption increases the likelihood of developing high risk adenomas or colorectal cancer.